Uchodźcze utopie we współczesnej literaturze światowej i Drzwi na Zachód Mohsina Hamida - Czernik, Jakub (Porównania, 2025)
In the 21st century, the experience of refuge is far more frequently associated with negative than with positive connotations. Ongoing events that compel vast numbers of people to abandon their homelands produce media portrayals and cultural representations marked by homelessness, poverty, displacement, disease, and death—images that profoundly shape public perceptions of contemporary migratory processes. In light of insufficient political responses to the challenges facing today’s refugees, humanitarian organizations have increasingly turned to artistic forms of expression to enhance the impact of awareness campaigns aimed at inspiring solidarity and exerting pressure on political authorities. An alternative approach suggests that, in order to counteract the reluctance of Western societies to accept refugees, it may be more effective to present refuge not solely as a tragic necessity but also as an opportunity for renewal and a fresh start in a new environment. Following this perspective, a number of literary and cultural texts have emerged after 2015 that draw on the well-established literary trope of the migrant’s success story—narratives that frame migration not merely as escape from the past but as the beginning of a meaningful new life. This article explores these issues primarily through an analysis of Mohsin Hamid’s novel Exit West (original edition 2017).